PELATIHAN AKUNTANSI DESA BAGI PARA APARATUR PEMERINTAH NEGERI DI WILAYAH KECAMATAN LEITIMUR SELATAN KOTA AMBON - Usmany, Paul; Loupatty, Linda Grace; Usmany, Alfrin E. M. (Komunitas Manajemen Kompetitif, 2024)
Community ServiceCommunity Service (PkM) is basically the social responsibility of the higher education academic community to help the community solveacademic community of higher education to help the community in solvingproblems faced or in developing their potentials.that they have. Within this framework, the community service activities ofcommunity service activities of the Faculty of Economics and Business Pattimura University organized